Is percutaneous drainage better than endoscopic drainage in the management of patients with malignant obstructive jaundice? A meta-analysis of RCTs - Bian, Cnogwen; Fang, Yuan; Xia, Jun; Shi, Lan; Huang, Hanfei; Xiong, Qiru; Wu, Ruolin; Zeng, Zhong (Frontiers in Oncology, 2023)
To compare the safety and efficacy of endoscopic retrograde cholangiopancreatography (ERCP) and percutaneous transhepatic cholangial drainage (PTCD) in the treatment of malignant obstructive jaundice, a systematic review and meta-analysis of published studies was undertaken to assess the differences between the two procedures in terms of efficacy and safety.rom November 2000 to November 2022, the Embase, PubMed, MEDLINE, and Cochrane databases were searched for randomized controlled trials (RCTs) on the treatment of malignant obstructive jaundice with ERCP or PTCD. Two investigators independently assessed the quality of the included studies and extracted the data.Six RCTs, including 407 patients, were included. The results of the meta-analysis showed that the overall technical success rate in the ERCP group was